THE EFFECT OF IMPLEMENTING TECHNOLOGY AND INNOVATION MANAGEMENT THROUGH ELECTRICITY LOSS APPLICATION INNOVATION ON CUSTOMER SERVICE AT PLN ULP BUKITTINGGI - Iman Rohmatan; Erwansyah (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2025)
Digital transformation is a strategic key for companies in improving the quality of public services, including in the electricity sector. This study aims to analyze the effect of digital technology implementation and innovation management on customer service, with the innovation of the Electricity Loss Application as an intervening variable at PT PLN (Persero) ULP Bukittinggi. The research method used is a quantitative approach with an associative causal design, involving 100 respondents who are active customers of the Electricity Loss Application. Data analysis was conducted using Structural Equation Modeling (SEM) based on Partial Least Squares (SmartPLS 4.0). The results of the study indicate that the application of digital technology does not have a significant direct effect on customer service. However, digital technology has a positive and significant effect on application innovation. Innovation management is proven to have a direct and indirect effect on customer service, through the innovation of the Electricity Loss Application as a mediating variable. This application innovation is proven to significantly mediate the effect between technology implementation and innovation management on improving customer service. These findings confirm that the success of digital transformation in public services is highly dependent on the existence of digital innovation that meets user needs. Therefore, the Electricity Loss Application can be an effective digital technology-based service innovation model in improving the quality of service in the electricity sector.